Simulation and Properties of the H-profile Meander System - Daškevičius, V.; Skudutis, J.; Štaras, S. (Elektronika ir Elektrotechnika, 2007)
The modified (H-profile) meander slow-wave structure is considered. The multi-conductor line method and the CST Microwave Studio software package are used for analysis of the system. Using the H-type profile (bending the lateral parts of the meander electrode in the opposite directions) we can reduce the electromagnetic coupling between the parts of the meander conductor at the sides of the meander electrode and, as a result, reduce dispersion of retardation factor and ripples of the transfer characteristic of the system. Means for further improvement of H-profile meander system are proposed. The H-profile meander system is the inhomogeneous structure. The characteristic impedance changes along the conductor of the meander electrode. In order to reduce the ripples of the transfer characteristic we must reduce the periodic change of the characteristic impedance.Ill. 7, bibl. 8 (in English, summaries in English, Russian and Lithuanian).